Peran Uang Dalam Persfektif Ekonomi Islam - Fitriani, Rika; Fatimawati, Fitri (CV. ITTC INDONESIA, 2024)
This research aims to understand the role of money in the perspective of conventional economics and Islamic economics, using qualitative research methods. This research explores the concept of money as a legal medium of exchange and its function in people's lives. In a conventional economic perspective, money is seen as the main medium for carrying out transactions, a store of value, and a tool for measuring the value of goods and services. However, in Islamic economics, the concept of money is not only seen from its function as a medium of exchange, but also from an ethical and moral perspective, where the use of money must be in accordance with sharia principles, including the prohibition of usury and an emphasis on social justice. This research found that the role of money in people's lives is very important, both in conventional and Islamic economics. However, in Islamic economics, money should not be the final goal, but rather a means to achieve just social and economic prosperity. Money must be used to support sustainable economic growth and a more equitable distribution of wealth, in accordance with the values ​​of justice and benefit in Islam. In conclusion, the role of money in the Islamic economy has a broader dimension than just a means of exchange, because it also takes into account moral and social aspects.